THE ROLE OF STATE CIVIL APPARATUS IN IMPROVING PUBLIC SERVICES (CASE STUDY OF NGAGEL DISTRICT OFFICE, SURABAYA CITY, EAST JAVA) - Safril Anamil Rizki; Misbahrudin Misbahrudin; Andi Ulil Abror; Sumrotul Hasanah; Riyan Sisiawan Putra (WORLDVIEW ( Development economic and sharia studies journal ), 2023)
As one of the country's most important components, ASN must continue to actively understand a task and its role in strengthening its position as one of the transformation agents in management. Also must continue to be able to see far ahead to see the direction and manage a better attitude. The issue of the role of the state civil apparatus in improving public services is the focus and objective of this qualitative study. These findings explain that the implementation of public services is actually developed as a component of the welfare of society as a whole and each work unit in its environment is fully responsible for all aspects of this process. ASN's additional task is to become one of the facilitators in the implementation of these public services, ensuring that those who need assistance can be served properly. Where in this study used qualitative methods with a subjective examination approach. The type of examination used in this exploration was explanatory research. The results of this study indicate that the State Civil Apparatus at the Ngagel Village Office has carried out its role as ASN, namely serving the state or providing good enough service to citizens with a sense of justice without discriminating between race, religion or ethnicity, and providing friendly functions and duties. and polite. However, the State Civil Apparatus at the Ngagel Kelurahan Office was not disciplined at work, as seen from the delay.